WATER DISINFECTION USING TiO2 UNDER SOLAR IRRADIATION - Galarza, P. (2002)
Water contaminated in plastic bottles was radiated with solar light. lt has analyzed the probable number by unit of volume of Fecal and Total Coliforms. The obtained results show that with a solar irradiation of average 700 W/m2 the disinfection is obtained in few hours.